Assessment of learning difficulties in the category of children with dyslexia - Trubus Raharjo; Supra Wimbarti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study is aimed to assess the diagnostic criteria for children with dyslexia. The diagnostic criteria are based on behavioral symptoms that appear in children with difficulty in reading and writing. The measurement of criteria of dyslexia is based on the criteria found in the specific learning difficulties category in DSM-5. Measurements were made of children who were considered to have learning difficulties as indicated by the inability and poor learning outcomes. Measurements were by testing the ability to read and write. Research used a qualitative approach with a case study method to obtain a description of the results. Research subjects were conducted on 65 elementary school students who had indications of learning difficulties. The results on the ability to read and write obtained as many as 28 students who were indicated to have criteria of dyslexia. Materials testing with aspects of phonological awareness and orthographic aspects. The next measurement is done by conducting an intelligence test using WISC III. Combining the results of measurements of reading and writing abilities and the results of intelligence tests are used to diagnose children with dyslexia, based on the criteria for indications of dyslexia taken from DSM-5. The results category on children with dyslexia can be diagnosed using one or more of the categories available on DSM-5